Evaluación de riesgos psicosociales en el personal operativo de los talleres del Gad de Baños de Agua Santa - Samaniego Jiménez, Víctor Hugo (2022)
The present investigation focuses on the problem detected in the workshops of the GAD Baños de Agua Santa, which presents problems with operational workers with situations of isolation, producing an imbalance in the worker and giving rise to high levels of stress: the investigation seeks to carry out an evaluation of the psychosocial risk factors and their incidence in work performance, this investigation is of a correlational type, in addition, the method used is inductive through research techniques such as field observation, bibliography and the survey as an instrument, it provides true information for the analysis of psychosocial risk factors through the tabulation tool provided by the Ministry of Labor, which reflects the high risk level of 60% in dimension N1 workload and pace, which will be used to perform the correlation with job performance by areas of the workshops s where their level of work performance is affected by a decrease of 13.47% in each area, giving a new level of work performance of 61.53%, percentages that help the security technician to mitigate the risks found in the Baños de GAD workshops. Holy water